Decationized polyplexes for gene delivery. (April 2015) - Novo, Luís; Mastrobattista, Enrico; van Nostrum, Cornelus F; Lammers, Twan; Hennink, Wim E
<x xml:space="preserve">Abstract</x> Gene therapy has received much attention in the field of drug delivery. Synthetic, nonviral gene delivery systems have gained increasing attention as vectors for gene therapy mainly due to a favorable immunogenicity profile and ease of manufacturing as compared to viral vectors. The great majority of these formulations are based on polycationic structures, due to their ability to interact with negatively charged nucleic acids to spontaneously form nanoparticles. In recent years, several polycationic systems have demonstrated high transfection in vitro. However, progress toward clinical applications has been slow, mainly because the cationic nature of these systems leads to intolerable toxicity levels, inappropriate biodistribution and unsatisfactory efficiency in vivo, particularly after systemic administration. Decationized polyplexes are a new class of gene delivery systems that have been developed as an alternative for conventional polycation-based systems. The major innovation introduced by decationized polyplexes is that these systems are based on neutral polymers, without any detrimental effect on the physicochemical stability or encapsulation ability, due to the transient presence of cationic charge and disulfide cross-links between the polymer chains by which the nucleic acids are physically entrapped in the particles. This editorial summarizes the most important features of decationized polyplexes and discusses potential implications for the development of new safe and efficient gene delivery systems.